2022
DOI: 10.1177/2515690x221116403
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Could Enhance the Effectiveness of Glibenclamide in Treating Diabetes and Preventing Diabetic Nephropathy: A Biochemical, Histological and Immunohistochemical Study

Abstract: Diabetes mellitus is an oxidative stress-related disease characterized by hyperglycemia and a variety of complications, including nephropathy. Vitamin D has variable functions extending beyond the calcium metabolism to prevent oxidative tissue damage. We aimed to investigate whether vitamin D supplements could enhance Glibenclamide's effectiveness in treating diabetes and minimize the risk of associated pathology. Wistar rats were divided into normal control (n = 10) and diabetic (n = 30), where animals receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Consistent with Atia et al (2022), the study by Lim et al (2021) reported lower plasma triglyceride and TC levels in the diabetic mice group after 12 weeks supplemented with 300 mg and 600 mg of vitamin D3. This study also showed that vitamin D3 supplementation lowers lipogenesis and inhibits lipid accumulation by improving β-oxidation.…”
Section: Changes In Lipid Profilesupporting
confidence: 66%
See 2 more Smart Citations
“…Consistent with Atia et al (2022), the study by Lim et al (2021) reported lower plasma triglyceride and TC levels in the diabetic mice group after 12 weeks supplemented with 300 mg and 600 mg of vitamin D3. This study also showed that vitamin D3 supplementation lowers lipogenesis and inhibits lipid accumulation by improving β-oxidation.…”
Section: Changes In Lipid Profilesupporting
confidence: 66%
“…The study also showed that vitamin D3 supplementation reduced liver TG content, while hepatic TC levels did not significantly change (Lim et al, 2021). Atia et al (2022) showed a significant decrease (p<0.001) in TC and TG levels in diabetic rats treated with eight weeks of cholecalciferol compared with untreated diabetic rats. Wahba et al (2021) showed that vitamin D3 significantly improved the markers of obesity and serum lipids such as serum TG, TC, and TC/HDL-C ratio profile compared to untreated metabolic syndrome rats (p<0.05).…”
Section: Changes In Lipid Profilementioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, numerous studies have linked vitamin D deficiency to B-cell dysfunction and insulin resistance (IR) in type 2 diabetes. [4,5] Therefore, the global increase in vitamin D deficiency may be related to the increasing prevalence of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with diabetes exhibited elevated urinary albumin and serum urea [ 62 ], as VDR overexpression can mitigate defective podocyte autophagy in DN via AMPK [ 63 ]. With vitamin D treatment, both urinary albumin and serum urea levels were diminished, and the production of inflammation-related cytokines, such as IL-6 and TNF-alpha, was downregulated [ 64 ]. Control mice displayed a significant presence of VDR in the nuclei of glomerular podocytes, while VDR levels were decreased in the DN group.…”
Section: Mechanistic Studiesmentioning
confidence: 99%